PENGARUH KARAKTERISTIK WIRAUSAHAWAN PEMULA DALAM UPAYA MENCAPAI KEBERHASILAN USAHA - Yayat Fitriani; S Suprianto; Ni Kadek Ayu Puspitasari (Jurnal Ekonomi & Bisnis, 2021)
Entrepreneurial characteristics are qualities that can be used as characteristics to identify a person from individual traits in the form of a person's personality. This research was conducted with the aim of knowing whether there is an influence of the characteristics of a beginner entrepreneur in an effort to achieve the success of a boba drink business in Sumbawa sub-district. The research method used is descriptive analysis method, and uses simple linear regression analysis method, and coefficient of determination. The data used in this study are primary and secondary data. The population in this study amounted to 7 respondents with a sampling technique that is by using a questionnaire. The data was processed statistically by using SPSS for windows program tools. The results of this study indicate that the constant value in the equation is 5,694 this means that if there is no change in entrepreneurial characteristics or is considered constant (fixed), then the success of the business is 5,694 units. ) of 0.748 with a significant value of 0.488. the coefficient of multiple linear determination (R2) is 0.101 or 10.1%, so the characteristics have no positive and significant effect on business success and entrepreneurial skills have no positive and significant effect on the success of boba beverage business in Sumbawa sub-district.